Synthesis of hydroxyl terminated liquid natural rubber by oxidative depolymerization of deproteinized natural rubber - Giang, Le Duc; Thao, Dinh Mong; Huong, Hoang Thi; Thu Hiep, Le Thi (Vietnam Journal of Science and Technology, 2016)
Hydroxyl terminated liquid natural rubber (HTLNR) was prepared by the depolymerization of deproteinized natural rubber (DPNR) in mixture of toluene and water at 60oC for 24 hours in the presence of ammonium persulfate as an initiator and tetrahydrofuran (THF) as a homogenizing agent. GPC analysis revealed that the number-average molecular weight (Mn) and weight-average molecular weight (Mw) of HTLNR were found to be 4.334×103 g/mol and 11.702×103 g/mol, respectively, with polydispersity index (PDI) of 2.7. The chemical structure of HTLNR was determined by FTIR and 1H-NMR and 13C-NMR spectroscopic analysis. The mechanism of depolymerization and hydroxylation of NR to form HTNR based on the analytical data is also suggested in this study.